Marking Technology of Energy Efficiency for Heating Ventilation and Air Conditioning - Kordyukov, M. (КНУБА, 2017)
For a number of reasons, the guidance documents on energy efficiency of HVAC systems, developed by the European institutions, are focused on heating systems. Development standards for energy efficiency of air-conditioning and ventilation systems is delegated to national regulators. In addition, there is an ability to define standards for energy efficiency in hot climate. Given global warming and European comfort indicators of residential and public premises, becomes relevant for Ukraine energy efficiency levels rationing HVAC technologies on the national level. The problem of marking the energy efficiency of ventilation and air conditioning technologies is relevant for Ukraine because the implementation of European standards for the comfort of residential and public premises requires the use of ventilation and air conditioning systems in most buildings.
Маркування технологій опалення, вентиляції та кондиціонування повітря за ступенем енергоефективності
Маркировка технологий отопления, вентиляции и кондиционирования воздуха по степени энергоэффективности
Keywords: energy efficiency HVAC; the level energy efficiency HVAC; reduction of greenhouse gas emissions systems HVAC; енергоефективність ОВК; рівень енергоефективності систем ОВК; зниження викидів парникових газів системами ОВК; энергоэффективность ОВК; уровень энергоэффективности систем ОВК; снижение выбросов парниковых газов системами ОВК; 697.9:628.87:504.05